In the name of Jefferson. Critical review of Denise Spellberg’s book Thomas Jefferson’s Qur’an - de Diego González, Antonio (THÉMATA. Revista de Filosofía, 2014)
Critical review of Denise Spellberg’s book Thomas Jefferson’s Qur’an